TubZIP28, a novel bZIP family transcription factor from Triticum urartu, and TabZIP28, its homologue from Triticum aestivum, enhance starch synthesis in wheat. Issue 5 (8th February 2020) - Song, Yanhong; Luo, Guangbin; Shen, Lisha; Yu, Kang; Yang, Wenlong; Li, Xin; Sun, Jiazhu; Zhan, Kehui; Cui, Dangqun; Liu, Dongcheng; Zhang, Aimin
Summary: Starch in wheat grain provides humans with carbohydrates and influences the quality of wheaten food. However, no transcriptional regulator of starch synthesis has been identified first in common wheat ( Triticum aestivum ) due to the complex genome. Here, a novel basic leucine zipper (bZIP) family transcription factor TubZIP28 was found to be preferentially expressed in the endosperm throughout grain‐filling stages in Triticum urartu, the A genome donor of common wheat. When TubZIP28 was overexpressed in common wheat, the total starch content increased by c. 4%, which contributed to c. 5% increase in the thousand kernel weight. The grain weight per plant of overexpression wheat was also elevated by c. 9%. Both in vitro and in vivo assays showed that TubZIP28 bound to the promoter of cytosolic AGPase and enhanced both the transcription and activity of the latter. Knockout of the homologue TabZIP28 in common wheat resulted in declines of both the transcription and activity of cytosolic AGPase in developing endosperms and c. 4% reduction of the total starch in mature grains. To the best of our knowledge, TubZIP28 and TabZIP28 are transcriptional activators of starch synthesis first identified in wheat, and they could be superior targets to improve the starch content and yield potential of wheat.